Evaluation of onion varieties in the Dominican Republic. - Morales, José Pablo; Navarro, Félix; Rondón, Félix; Báez, Clemente; Genao, Ricardo (Agronomía Mesoamericana, 2006)
A field study was conducted in order to evaluate 16 onion crops for their yield, grade and susceptibility to pests and diseases under field conditions in San Cristóbal, Dominican Republic. The cultivars 'Texas Grano 438', 'Liberty', 'Lexus', 'Domingo', 'Serrana', 'Mercedes', 'Yellow Granex', 'Cougar', XPH 6700, 'Sebaqueña', 'Contessa', 'White Hawk', 'Diamante', 'Red Creole', 'Híbrido Rojo' and 'Sivan' were distributed in randomized complete blocks with three repetitions. Experimental units consisted of two double rowsthree meters in length. 'Red Creole', 'Yellow Granex' and 'Contessa' were utilized as prototypes for the red, yellow, and white onion crops, respectively. Onion crops were managed following a medium level technology package recommended for the zone. The variables evaluated were early development, diameter of thebulb neck at harvest, number of rings per bulb, incidence of pests and diseases, yield grades, total commercial yield, percentage of twin bulbs and percentage of rotten bulbs after curing. Statistical analysis revealed that among yellow cultivars, the materials with the best attributes of yield and bulb quality were 'Texas Grano 438', 'Lexus', 'Liberty' and XPH 6700. The yield of the of 'Texas Grano 438'. Among white onion crops, 'Diamante' and 'Contessa' were significantly better than 'Sebaqueña' and 'White Hawk' in terms of early development and/or yield. For the red crops, 'Red Creole' was significantly inferior than 'Híbrido Rojo' and 'Sivan' in bulb grade and yield.